The Link Between Parental Absence and Poor Reading Comprehension: Evidence From the Left-Behind Children in Rural China - Xiaofeng, Ma; Wenhui, Deng; Aibao, Zhou (Frontiers in Education, 2018)
Family environment affects children’s reading ability. In poverty-stricken parts of rural China, some parents have been migrant workers for many years. It is common for left-behind children to have one or both parents permanently missing. This study explores the impact of parental absence on children’s reading comprehension. We measured the reading comprehension of 903 children (467 left-behind and 436 parented), using the Chinese Primary School Students’ Reading Comprehension Ability Scale. After controlling for the parents’ levels of education, reading input, and interest variables, we found that children with absent parents had significantly lower reading comprehension scores than parented children; they struggled to understand chapter layout, the author’s intentions, writing technique, evaluation, and appreciation. While children with absent fathers received the same scores as parented children, those with absent mothers received significantly lower scores. Clearly, absent mothers have a greater impact on children’s reading comprehension than absent fathers.